1988
DOI: 10.1111/j.1365-2621.1988.tb09264.x
|View full text |Cite
|
Sign up to set email alerts
|

Inability to Transfer Antibiotic Resistance in Escherichia coli on Meat Surfaces

Abstract: The surfaces of beef and chicken samples were inoculated with a mixture of a donor (resistant to tetracycline, streptomycin, chloramphenicol, ampicillin, neomycin and sulphonamide), and a recipient strain of Eschetichia coli. Meats were maintained at 20°C and 4°C and sampled daily. Transfer of antibiotic resistance could not be demonstrated at either temperature. The recipient strain survived without significant growth at 4°C but failure to transfer antibiotic resistance at 20°C was considered to be due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Although attachment to meat surfaces is readily demonstrable, the extent of interaction during spoilage has not been well established. Observations of microcolony formation by various species (Yada and Skura, 1982;Firstenberg-Eden et al, 1979;Stone and Zottola, 1985;Mattila et al, 1988) and the secretion of extracellular material (Fraser and Gilmour, 1986) indicate active colonization of the meat surface. Studies were needed to determine whether attachment is an incidental event or if meat surfaces are specifically colonized by spoilage microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Although attachment to meat surfaces is readily demonstrable, the extent of interaction during spoilage has not been well established. Observations of microcolony formation by various species (Yada and Skura, 1982;Firstenberg-Eden et al, 1979;Stone and Zottola, 1985;Mattila et al, 1988) and the secretion of extracellular material (Fraser and Gilmour, 1986) indicate active colonization of the meat surface. Studies were needed to determine whether attachment is an incidental event or if meat surfaces are specifically colonized by spoilage microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Part of the persistence in the meat plant environment may, at least in part, be explained by cross-resistance with sanitation products, particularly through multidrug efflux pumps [101,110,121]. In an early (1988) study, Mattila et al [122] investigated the transfer of antibiotic resistance in E. coli on the surface of meat at 20 and 4 • C. They concluded that the lack of transfer between donor and recipient cells was due to the sessile growth on the meat surface which prevented the cell contact necessary for the transfer of genetic materials. Van Meervenne et al [123] indicated that a threshold cell density is necessary for the transfer of plasmid-bearing antibiotic resistance on cooked ham.…”
Section: From Pig To Meatmentioning
confidence: 99%
“…Since tet (M) was already successfully transferred from meat isolates in vitro (Gevers and others 2003), genetic transfer between tet (M) carriers and initially tet (M)‐negative bacteria during storage might further increase the tet (M) contents at retail. Conditions during refrigeration are thought to be unfavourable to bacterial conjugation (Mattila and others 1988; Novotny and Lavin 1971), but this was not assessed for psychrotrophic bacteria, which are metabolically active at low temperatures.…”
Section: Future Prospects: Epidemiology and Genetic Transfermentioning
confidence: 99%